Humanisme Dan Tantangan Kehidupan Beragama Abad Ke 21 - Mulyana Mulyana (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2016)
This article aims to discuss the issue of "how important Humanism religious life of the 21th century". Among the results was the word humanism temuanaya when seen from history before or after the time of scholastic renaissance, has a positive purpose and its impact can be felt to this day. To create a human being has dignity, the theme of humanism should be lifted, therefore the theme of humanism flourished before the 19th century as a forerunner to the renaissance. But with a growing era of many figures that interpret the meaning of humanism itself. Tertebut interpretation of which are still in kolidor approach to history, there is also the ekstrime or the so-called secular humanism that interprets humanism with methods that result in contradictory to religion, and this has led to the pros and cons of the theme of humanism.